Communication Style of Imigrant Dai in Da’wah - Ummi Kulsum; Bobby Rachman Santoso (Dakwah Institut PTIQ Jakarta, 2023)
Islam is the religion with the largest percentage in Indonesia. This majority makes Indonesia home to many dai, each with their own styles and ways. In addition to local preachers, there are dai who come from abroad, namely Sheikh Ali Jaber. He preaches by paying attention to local wisdom and tolerance. Sheikh Ali Jaber, who comes from Arabia, has a large number of ma'du in Indonesia. The popularity of his da'wah is because Sheikh Ali Jaber has a unique da'wah method compared to local dai in Indonesia. However, he had become a controversy since after the stabbing incident by someone while da’wah. This study uses qualitative research with a library research approach to reveal the communication style and implications of Sheikh Ali Jaber's da’wah. The primary data used are writings, social media, news, and journals about Sheikh Ali Jaber. The results showed that in delivering his da'wah, Sheikh Ali Jaber used Qaulan Layyinan, Qaulan Kariman, and Qaulan Balighan. While the da'wah is delivered by means of Hikmah, Mauidhah Hasanah, and Mujadalah, The community considers that the da'wah carried out by Sheikh Ali Jaber is moderate, reflects peace, and is polite (it does not take sides with organizations or da'wah institutions). Sheikh Ali Jaber in carrying out his da'wah is more open and also assimilate to all Muslim circles without distinguishing ORMAS and other religious sects.